Dampak Pembangunan Minapolitan Terhadap Kinerja Lalu Lintas - Muhamad Yusuf; Anton Budiharjo; Mohammad Archi Maulyda (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
The development of the minapolitan tourist area in Semarang City, is expected to generate attraction and generation of new trips. The development of this area will have an impact on the performance of the surrounding traffic. The purpose of this research is to analyze and predict the impact of traffic due to the development of the minapolitan area and provide recommendations for mitigation. Primary data collection is carried out through direct field surveys, including instantaneous speed surveys, inventory of sections and intersections, traffic volume, public transport and pedestrians and secondary data obtained from data from related agencies. The impact during the construction period is the mobilization of heavy equipment, the pull, and generation of worker activities, safety, and health issues. Meanwhile, during the operational period, namely the availability of parking space, pedestrian activity, geometric roads and entrance, and exit design as well as traffic safety and smoothness, the performance of sections and intersections, has increased from the existing stage, the construction period, the operational period to the next 5 years from the operational period. The results of the analysis show that minapolitan development will cause travel attraction of 103.31 pcu/hour and a generation of 102.82 pcu/hour.